2004
DOI: 10.1088/0967-3334/25/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cerebral haemodynamics by near-infrared spectroscopy in young healthy volunteers reveals posture-dependent spontaneous oscillations

Abstract: Autonomic reflexes enable the cardiovascular system to respond to gravitational displacement of blood during changes in posture. Spontaneous oscillations present in the cerebral and systemic circulation of healthy subjects have demonstrated a regulatory role. This study assessed the dynamic responses of the cerebral and systemic circulation upon standing up and the posture dependence of spontaneous oscillations. In ten young healthy volunteers, blood pressure and cerebral haemodynamics were continuously monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 26 publications
11
102
0
Order By: Relevance
“…The behavior of oscillations at this frequency has been widely investigated [15,16], particularly in the context of vasomotion, whereby spontaneous oscillations in vascular tone are observed [17]. Payne et al [6], also showed that this is frequency at which the magnitude of the ABP-O2Hb transfer function is greatest, thus most likely providing the largest signal and highest robustness to noise, and it is the frequency component investigated in the study by [18], which provides, to the best of our knowledge, the only other previous measure of the phase angles between ABP and O2Hb/HHb in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of oscillations at this frequency has been widely investigated [15,16], particularly in the context of vasomotion, whereby spontaneous oscillations in vascular tone are observed [17]. Payne et al [6], also showed that this is frequency at which the magnitude of the ABP-O2Hb transfer function is greatest, thus most likely providing the largest signal and highest robustness to noise, and it is the frequency component investigated in the study by [18], which provides, to the best of our knowledge, the only other previous measure of the phase angles between ABP and O2Hb/HHb in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…amplitude, frequency, phase) can be modulated by the stimulus/task to some degree. For example, it was shown that the amplitude of LF and VLF oscillations depend on the activity state (rest vs. task) (Obrig et al, 2000a), sleep stage (Näsi et al, 2011), body posture (Tachtsidis et al, 2003(Tachtsidis et al, , 2004, or age of the subject (Peng et al, 2008;Safonova et al, 2004). Thus, although these oscillations arise spontaneously, their stimulus/task-evoked modulation capability leads to the conclusion that they may also be part of the systemic activity type 1 and type 2 (SC2-3).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…The mechanical mounting system is connected to a seat with an adjustable back incline. The seat provides comfort and also the option of keeping the subject in a supine position during studies which can help reduce certain physiological noise effects such as the Mayer wave [10]. The original headrest of the seat was replaced by a mechanical framework to cradle the head and also to support and position the optodes as shown in figure 7.…”
Section: Resultsmentioning
confidence: 99%